Analisis Kebocoran Pipa Terhadap Kinerja Mesin Boiler DUNPHY TD 530 YML VK - Muhammad, Anovan Fadhil; Adiwibowo, Priyo Heru (TURBO [Tulisan Riset Berbasis Online], 2025)
This study aims to analyze the energy efficiency and capacity optimization of the TD 530 YML VK boiler after the occurrence of damage in the combustion system, specifically pipe leaks. The research was conducted by monitoring the boiler's condition before and after the leak, as well as after repairs were carried out. The methods used include collecting data on the leak, calculating energy efficiency, and evaluating fuel consumption. The results show that pipe leaks caused a 10% decrease in efficiency and an 11.1% increase in fuel consumption. After the repair, efficiency improved to 95% of the optimal condition, reducing fuel consumption by 5.31% for Diesel Oil and 5.26% for Natural Gas. The conclusion of this study is that repairs can enhance energy efficiency and reduce fuel consumption, although the performance does not fully return to the pre-leak optimal state